Factors influencing adolescents’ decision-making about COVID-19 vaccination: a systematic review with qualitative synthesis - Moreira da Cunha, Nayara; Tzirita, Sofia; Gobbo, Elisa; Herzig van Wees, Sibylle (Frontiers in Public Health, 2025)
IntroductionAttitudes towards vaccination are influenced by a broad range of factors, yet little is known about the drivers shaping adolescents’ vaccination beliefs. The aim of this study was to qualitatively explore the factors influencing adolescents’ individual decision-making towards COVID-19 vaccination.MethodsA systematic review was conducted using Medline, Web of Science, Sociological Abstracts, and Publicly Available Content Database. Studies on attitudes, beliefs, and perceptions of adolescents regarding COVID-19 vaccines were included. The JBI Critical Appraisal Checklist was used for quality assessment, followed by thematic synthesis of the included studies.ResultsIn total, 13 studies were included, revealing 5 key themes: (1) Limited vaccine literacy influences adolescents’ attitudes towards COVID-19 vaccines; (2) Family, peers, and community strongly influence adolescents’ COVID-19 vaccine decision-making; (3) Different levels of trust in vaccine providers and governments influence adolescents’ attitudes towards COVID-19 vaccines; (4) Desire to go back to normality influences adolescents’ COVID-19 vaccine attitudes towards vaccine acceptancy; (5) Autonomy influences adolescents’ COVID-19 vaccine decision-making.DiscussionThe review findings suggest that vaccine acceptance among adolescents could be improved through tailored and accessible vaccine literacy messaging, addressing structural mistrust, and empowering adolescents to make autonomous health decisions that take into account diverse contexts and populations.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024512197, identifier CRD42024512197.